An Analysis of the Suitability of Science Laboratory Management at the Junior High School Level Based on National Education Standards - Rina Fitriani; Putri Syarifa; Ai Anisa Asaidah; Fauzan Aninnajib Basri; Winda Ismi; Romy Faisal Mustofa; Liah Badriah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aimed to evaluate the suitability of science laboratory management at the junior high school level based on the National Education Standards (SNP) and to identify priority areas for improvement. A qualitative case study combined with descriptive quantitative evaluation was conducted at a private junior high school in Tasikmalaya, Indonesia. Data were collected through structured observations, semi-structured interviews, and document analysis using instruments developed from SNP indicators. The findings revealed that the overall suitability of science laboratory management reached 57.89%, indicating a Moderately Suitable category. The highest levels of compliance were found in the availability of electricity and water (86%) and equipment inventory (81%), while laboratory regulations, layout, and procurement of equipment and materials were categorized as suitable (75%). However, several aspects remained suboptimal, particularly laboratory utilization, organization, equipment maintenance, funding, monitoring and evaluation, documentation, and cleanliness. The lowest scores were identified in laboratory safety and security (38%) and laboratory personnel (33%), indicating critical weaknesses requiring immediate attention. These findings suggest that although several management components have complied with the National Education Standards, significant improvements are still needed, particularly in occupational safety, staffing, preventive maintenance, and continuous quality monitoring. Strengthening these aspects is expected to improve laboratory effectiveness and better support practical science learning in junior high schools.